Assessment of antigen-specific T cell recall responses in non-human primates using a composite AIM assay - Schmidt, Jan M.; Prasad, Mayuri; Degner, Kenna; Schiavo, Rebecca; Repic, Allison; Little, Lauren; Israel, Laura; Chen, Feng; Hansen, Regine; Karle, Anette C.; Leenhouts, Kees; Sørensen, Poul; et al. (Frontiers in Immunology, 2025)
IntroductionCharacterizing antigen-specific T cell responses is essential for understanding the immunogenicity of biotherapeutics and mitigating drug-specific immune reactions.MethodsThis study describes a flow cytometry composite Activation-Induced Marker (cAIM) assay for cynomolgus monkeys that allows quantification of T cell recall responses to multiple antigens using up to ten AIM pairs. The procedure incorporates two composite metrics (cAIM-index and cAIM-score) that facilitate the summation of T cell recall responses into interpretable numeric values, reducing reliance on multiple graphical comparisons. The assay is compatible with human and mouse samples and can utilize peripheral blood mononuclear cells or whole blood. Additionally, the method is well suited for the mass cytometry platform, enabling the detection of antigen-specific CD4+ and CD8+ T cell recall responses while providing deep immunophenotype information and consuming minimal blood sample volumes.ResultsThe assay successfully enables quantification of antigen-specific T cell recall responses across multiple antigens and species, while composite metrics streamline interpretation.DiscussionThese protocols shall support preclinical and clinical immunogenicity assessments, advancing biotherapeutic development.